The Effect of Brand Image and Service Quality on Customer Loyalty: The Mediating Role of Customer Satisfaction in Grab Ride-Hailing Services - Fedro Diaz Camsal; Osly Usman; Munawar Asikin (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
Online transportation services are expanding at such a fast rate that there is a rivalry amongst the online transportation providers. However, customer loyalty is key to overcome the problems when it comes to customer service and complaints from customers, and this is another challenge that needs to be addressed with Grab. This is a quantitative study aimed at understanding the impact of brand image and service quality on customer loyalty via customer satisfaction. The data is collected by a questionnaire distributed in participants in the area of Grab users, Jabodetabek and analyzed by SmartPLS 4.0. The results indicate that service quality is not significant to the customer loyalty; however, brand image and customer satisfaction are significant. Furthermore, customer satisfaction also mediated between service quality and brand image towards customer loyalty. These results echo the view that satisfaction and brand image are the most critical factors that impact on customer loyalty other than service quality.